1999
DOI: 10.1103/physrevb.59.11151
|View full text |Cite
|
Sign up to set email alerts
|

High-field magnetization and magnetoresistance ofLa0.5Sr1.5MnO

Abstract: ͑Received 21 December 1998͒Measurements of magnetization and magnetoresistance have been made for crystals of La 0.5 Sr 1.5 MnO 4 with use of pulsed magnetic fields up to 40 T. Application of high magnetic field causes metamagnetic transitions below 217 K and concomitantly the colossal magnetoresistance effect. At low magnetic fields, change of resistivity is expressed well by a formula for hopping conduction whose activation energy decreases in proportion to the square of magnetization. In high fields, temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 22 publications
(15 reference statements)
1
17
0
Order By: Relevance
“…The anomalies in the thermal expansion suggesting a rearrangement of the orbital occupation induced by the magnetic interaction resemble recent observations on LaTiO 3 26,27 and on Ca 2 RuO 4 . 28 In these compounds, one finds an enhancement of an octahedron distortion upon approach of the Néel order.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…The anomalies in the thermal expansion suggesting a rearrangement of the orbital occupation induced by the magnetic interaction resemble recent observations on LaTiO 3 26,27 and on Ca 2 RuO 4 . 28 In these compounds, one finds an enhancement of an octahedron distortion upon approach of the Néel order.…”
supporting
confidence: 69%
“…Like the perovskite LaMnO 3 , La 1.0 Sr 1.0 MnO 4 exhibits an antiferromagnetic order. Kawano et al report a small ordered moment of only 0.8 µ B 9 compared to the value of 3.87(3) observed in LaMnO 3 .…”
mentioning
confidence: 98%
“…Tokunaga et al 47 noted that the formula ͑4͒ may be applied to hopping conductivity although the preexponential factor is not of course min Ϫ1 . They found that the change of resistivity in La 1/2 Sr 3/2 MnO 4 agrees well with the simple model of hopping conduction with activation energy varying as m 2 if mр0.7.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…9,[33][34][35][36] Magnetic ordering of the CE type occurs below T N = 110 K. 9 Compared to the perovskite manganites, the COO state is exceptionally stable in La 1/2 Sr 3/2 MnO 4 and only very high fields of the order of 30 T can melt the ordered state, implying negative magnetoresistance effects. 37 Good metallic properties are, however, never achieved in the single-layered manganites La 1−x Sr 1+x MnO 4 neither by magnetic field nor by doping. 38,39 In a recent work, we have studied the magnetic excitation spectrum of the CE-type ordering in La 1/2 Sr 3/2 MnO 4 at low temperatures.…”
Section: Introductionmentioning
confidence: 99%